The effect of STAD learning model using the finger-counting method on students’ multiplication skills - Alvira Althamiranda; Hafiziani Eka Putri; Elvara Salsabilla Chaisa; Lufinda Amalia; Nurul Aini; Sabrina Shafa Aulia; Annisa Salsabila Nurista (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2024)
Students may encounter difficulties when solving basic multiplication problems. They proficiently recalled the entire multiplication table but struggled to locate specific results without reciting the whole table. Those interconnected challenges highlight the importance of implementing comprehensive teaching strategies. This study aims to support fourth-grade students' multiplication skills at SDN 3 Sindangkasih by applying the STAD learning model and finger-counting method. This study employed a quasi-experimental design with both control and experimental groups. Results show that the experimental class's average score improved significantly from 57 to 73 after treatment, while the control class's score increased slightly from 62 to 62.5, indicating no significant change. The significance value of the Wilcoxon test for the control group's pretest and posttest scores is 0.763, greater than 0.05, indicating no significant difference in average scores before and after the class. In contrast, the analysis for the pretest and posttest scores of the experiment class reveals a significant difference in scores (p = 0.000 < 0.05), indicating that the STAD learning model combined with the finger-counting method significantly improves students' multiplication skills. The findings suggest that the finger-counting method effectively supports students' multiplication abilities by providing a tangible and interactive approach to learning.